Kaolinite-based antibacterial medical gauze and preparation method thereof
Micron-scale kaolinite was prepared by step-step intercalation-ultrasonic peeling-level centrifugation method, and combined with antibacterial metal ions, the problems of uneven loading and unstable binding of kaolin hemostatic gauze materials were solved, achieving efficient antibacterial effects.
Patent Information
- Application Number
- CN202411315623.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
AI Technical Summary
The functional materials of existing kaolin hemostatic gauzes have uneven loads and are unstable in combination with the gauze, which makes it impossible to fully play the role of the functional materials.
Micron-scale sheet kaolinite was prepared by step-by-step intercalation-ultrasonic peeling-level centrifugation method, and it was soaked in a mixed solution of polyvinylpyrrolidone and sodium carboxymethylcellulose after modification. In medical nonwoven fabrics, kaolinite-based metal ion antibacterial materials are formed.
The uniform distribution and stable combination of kaolinite antibacterial materials on the surface of medical gauze is achieved, the antibacterial activity is enhanced, and the functional limitations of single metal ions in complex biological environments are overcome.
Smart Images

Figure CN119194846A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical gauze, in particular to a kaolinite-based antibacterial medical gauze and a preparation method thereof. Background Art
[0002] Functional medical gauze usually immerses medical non-woven fabrics in a suspension of functional materials that are stirred evenly, and then presses and dries the soaked gauze to obtain kaolin hemostatic gauze. For example, a method for preparing kaolin hemostatic gauze disclosed in a Chinese patent with application number 202211182898X records that kaolin hemostatic material is made into a suspension, and then the medical non-woven fabric is immersed in the stirred suspension, and the upper and lower edges are soaked once; press and dry the soaked gauze to obtain kaolin hemostatic gauze. The kaolin hemostatic gauze prepared by the above technology has uneven functional material load and unstable combination with gauze, which results in the inability to give full play to the functional role of the functional material. Summary of the invention
[0003] The object of the present invention is to provide a kaolinite-based antibacterial medical gauze and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.
[0004] The method for preparing a kaolinite-based antibacterial medical gauze of the present invention comprises the following steps:
[0005] Step S1, preparing micron-sized flaky kaolinite by a step-by-step intercalation-ultrasonic exfoliation-grading centrifugation method;
[0006] Step S2, loading antibacterial metal ions on micron-sized flaky kaolinite after modification with polyacrylic acid to obtain kaolinite-based metal ion antibacterial material;
[0007] Step S3, preparing a mixed solution of kaolinite-based metal ion antibacterial material, polyvinyl pyrrolidone and sodium carboxymethyl cellulose, then soaking the medical non-woven fabric in the mixed solution, taking it out and drying it to obtain kaolinite-based metal ion antibacterial medical gauze.
[0008] Furthermore, the concentration of the mixed solution of polyvinyl pyrrolidone and sodium carboxymethyl cellulose polymer is 0.1% to 1%.
[0009] Furthermore, the mass ratio of polyvinyl pyrrolidone to sodium carboxymethyl cellulose is 1-3:1-3.
[0010] Furthermore, in the mixed solution of step S3, the concentration of kaolinite-based metal ion antibacterial material is 10 mg / mL.
[0011] Furthermore, the antibacterial metal ions include one or more of silver, zinc and gallium.
[0012] Furthermore, the specific operation of step S2 is: adding the polyacrylic acid aqueous solution dropwise into the kaolinite aqueous dispersion to stir the reaction, then adding the antibacterial metal ion solution to stir the reaction, and after the reaction is completed, centrifugation washing and freeze drying are performed to obtain the kaolinite-based metal ion antibacterial material.
[0013] Furthermore, the mass ratio of polyacrylic acid to kaolinite is 0.5-3:1, the concentration of antibacterial metal ions is 1 mol / L, and the reaction time is 3-6 h.
[0014] Furthermore, in step S1, the intercalation agents used in the stepwise intercalation process are dimethyl sulfoxide and urea, and the intercalation reaction time is 20 to 24 hours; and\or,
[0015] The ultrasonic power during the ultrasonic stripping process is 1200-1500W, the ultrasonic time is 4-6h, and the reaction temperature is 50-60°C.
[0016] Furthermore, in step S1, the centrifugal speed during the graded centrifugation process is 1000-6000 rpm, and the centrifugal time is 3-5 min.
[0017] A kaolinite-based antibacterial medical gauze prepared by the above-mentioned preparation method.
[0018] The present invention utilizes the adhesiveness and film-forming property of polyvinyl pyrrolidone (PVP) / sodium carboxymethyl cellulose (CMC) to promote the rapid dispersion and stable loading of kaolinite-based metal ion antibacterial materials on the surface of medical non-woven fabrics. In addition, the negatively charged functional groups in PVP can produce strong electronic interactions with positively charged metal ions, and work together with PAA to avoid the short contact time between metal ions and bacterial hosts that weakens the antibacterial activity; and in addition to the physical adhesion effect, the bond and interaction between PAA / PVP / CMC polymers make the kaolinite antibacterial material more firmly and stably combined on the surface of medical gauze.
[0019] The present invention realizes the separation and collection of micron-sized flaky kaolinite by using the intercalation stripping and graded centrifugation methods, which is helpful to solve the key problems of large size and poor uniformity of kaolinite.
[0020] The present invention utilizes the synergistic effect between silver, zinc and gallium ions to overcome the limitation of the limited antibacterial function of a single metal ion in a complex biological environment.
[0021] The high adsorption and surface activity of PAA-modified kaolinite flakes enable large-scale loading and uniform distribution of metal ions, which is beneficial to maintaining the long-term efficacy of metal ion antibacterial materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The particle size distribution diagram of kaolinite collected in Example 1;
[0023] Figure 2 The scanning electron microscope image (a) and particle size distribution histogram (b) of the kaolinite collected in Example 1;
[0024] Figure 3 This is a photo of the kaolinite-based silver-zinc composite ion antibacterial medical gauze prepared in Example 4. DETAILED DESCRIPTION
[0025] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.
[0026] Embodiment 1:
[0027] This embodiment uses the method of intercalation stripping and graded centrifugation to achieve the separation and collection of micron-sized flaky kaolinite.
[0028] Take 90mL of dimethyl sulfoxide (DMSO) and 10ml of deionized water and put them into a reaction bottle, weigh 10g of Kaol and add them to the above reaction bottle. Stir the reaction for 24h in a 60℃ water bath. After the reaction is completed, centrifuge, wash the resulting precipitate with anhydrous ethanol three times and dry it at 60℃ for 24h to obtain a DMSO-intercalated kaolinite complex (Kaol-DMSO). Weigh 39g of urea (Urea) and put it into a reaction bottle, add 50ml of deionized water, stir until dissolved, and prepare a 13mol / L saturated urea solution. Put 5g of Kaol-DMSO sample into the above reaction bottle, add 50ml of urea solution, and stir at room temperature for 24h. After the reaction is completed, centrifuge at 8000rpm, wash the resulting precipitate with anhydrous ethanol three times and dry it at 60℃ for 24h to obtain a Urea-intercalated kaolinite complex (Kaol-Urea). Take 2g Kaol-Urea and disperse it in 200mL deionized water. Use an ultrasonic extractor to ultrasonicate for 5h at 60℃ with a power of 1500W. After the ultrasonic stripping reaction, the resulting solution was centrifuged at 1000rpm for 3min, and then the lower precipitate and the upper supernatant were separated. The separated supernatant was centrifuged at 2000rpm for 3min, and the lower precipitate was collected and characterized for particle size distribution and morphology.
[0029] Figure 1 This is the particle size distribution result of the kaolinite screened in this example. The particle size distribution of the kaolinite after screening is concentrated at 1.463 μm. Scanning electron microscope image ( Figure 2 ) further confirmed the particle size characterization results, and it was observed that there were still smaller kaolinites attached to the surface of the micron-sized kaolinite.
[0030] Embodiment 2:
[0031] This example prepares kaolinite-based metal ion antibacterial material.
[0032] 200 mg of polyacrylic acid (PAA) was weighed and added to 20 mL of deionized water, and ultrasonically dispersed into a 10 mg / mL polyacrylic acid (PAA) aqueous solution, which was labeled as solution A. 100 mg of kaolinite (Kaol) collected in Example 1 was weighed and added to 100 mL of deionized water, and ultrasonically dispersed into a 1 mg / mL kaolinite dispersion, which was labeled as solution B. 1.698 g of AgNO3 was weighed and added to 100 mL of deionized water, and ultrasonically dispersed into a 1 mol / L mixed metal ion solution, in which Ag + The concentrations of the two solutions were all 1 mol / L, and the solution was marked as solution C. Solution A was added dropwise to solution B and stirred at room temperature for 6 h. After stirring, the solution was centrifuged and washed three times with deionized water to obtain PAA-modified kaolinite (PAA / Kaol). Subsequently, PAA / Kaol was dispersed in solution C and stirred at room temperature for 6 h. After stirring, the reaction product was centrifuged and washed three times with deionized water, and the product after centrifugal washing was freeze-dried to obtain a kaolinite-based silver ion antibacterial material, which was marked as Ag@PAA / Kaol.
[0033] Similarly, in the preparation of kaolinite-based zinc ion antibacterial material (Zn@PAA / Kaol), 1.698 g AgNO3 was replaced by 2.975 g Zn(NO3)2 6H2O.
[0034] Similarly, in the preparation of kaolinite-based gallium ion antibacterial material (Ga@PAA / Kaol), 1.698 g AgNO3 was replaced by 2.557 g Ga(NO3)3.
[0035] Similarly, in the preparation of kaolinite-based silver-zinc composite ion antibacterial material (AgZn@PAA / Kaol), 1.698 g of AgNO3 was replaced by 1.698 g of AgNO3 and 2.975 g of Zn(NO3)2 6H2O.
[0036] Similarly, in the preparation of kaolinite-based silver-gallium composite ion antibacterial material (AgGa@PAA / Kaol), 1.698 g AgNO3 was replaced by 1.698 g AgNO3 and 2.557 g Ga(NO3)3.
[0037] Similarly, in the preparation of kaolinite-based zinc-gallium ion antibacterial material (ZnGa@PAA / Kaol), 1.698 g of AgNO3 was replaced by 2.975 g of Zn(NO3)2 6H2O and 2.557 g of Ga(NO3)3.
[0038] Embodiment 3:
[0039] This embodiment optimizes the modification process of medical non-woven gauze.
[0040] First, different masses of polyvinyl pyrrolidone (PVP) and sodium carboxymethyl cellulose (CMC) were dissolved in deionized water to prepare a CMC / PVP mixed aqueous solution with a certain mass fraction, and the mass ratio is shown in Table 1. Then, a series of kaolinite (Kaol) / polyvinyl pyrrolidone (PVP) / sodium carboxymethyl cellulose (CMC) polymer mixed solutions were prepared, in which the concentration of kaolinite was 1 mg / mL. After soaking the 2×2 cm medical non-woven fabric in the mixed solution for 5 min, it was transferred to a 60°C oven for drying to obtain a kaolinite-based medical non-woven gauze. The mass of the medical non-woven fabric before and after soaking was weighed respectively, and the mass difference before and after soaking (Δmg) was used to evaluate the loading performance of CMC / PVP mixed solutions with different mass fractions and ratios. The results are shown in Table 2. When the mass fraction of CMC / PVP is 0.7% and the mass ratio is 2:3, the loading effect of the modified medical non-woven fabric is the best. At the same time, the water absorption performance of the modified medical non-woven fabric is evaluated by the water absorption. The kaolinite-based medical non-woven gauze obtained above was placed in 50mL deionized water for 5min, and the kaolinite-based medical non-woven gauze was taken out with tweezers and hung on a thin rope. After no liquid dripped on the cotton fabric, the mass of the cotton fabric after water absorption was weighed. The water absorption performance of CMC / PVP mixed solutions with different mass fractions and ratios was evaluated by the mass difference (Δg) before and after water absorption. The results are shown in Table 3. The water absorption of kaolinite-based medical non-woven gauze was basically maintained at 0.5g. Therefore, the process parameters of CMC / PVP mass fraction of 0.7% and mass ratio of 2:3 were selected to modify the medical non-woven gauze.
[0041] Table 1 Mass ratio of CMC to PVP in CMC / PVP mixed solution
[0042]
[0043] Table 2 Kaolinite loading (Δmg) of CMC / PVP polymer mixed solution modified medical non-woven gauze
[0044]
[0045]
[0046] Table 3 Water absorption of CMC / PVP polymer mixed solution modified medical non-woven gauze (Δg)
[0047]
[0048] Embodiment 4:
[0049] This example prepares kaolinite-based metal ion antibacterial medical gauze.
[0050] 100 mg of kaolinite-based silver ion antibacterial material (Ag@PAA / Kaol) was ultrasonically dispersed in 100 mL of a CMC / PVP polymer mixed solution with a mass fraction of 0.7% and a mass ratio of 2:3, and then a 1×1 cm medical non-woven fabric was immersed in the mixed solution for 5 min, and finally transferred to a 60°C oven for drying to obtain kaolinite-based silver ion antibacterial medical gauze (Ag@PAA / Kaol-NWS). Using the same method, kaolinite-based zinc ion antibacterial medical gauze (Zn@PAA / Kaol-NWS), kaolinite-based gallium ion antibacterial medical gauze (Ga@PAA / Kaol-NWS), and kaolinite-based silver-zinc composite ion antibacterial medical gauze (AgZn@PAA / Kaol-NWS) were obtained respectively (such as Figure 3 As shown), kaolinite-based silver-gallium composite ion antibacterial medical gauze (AgGa@PAA / Kaol-NWS) and kaolinite-based zinc-gallium ion antibacterial medical gauze (ZnGa@PAA / Kaol-NWS).
[0051] Embodiment 5:
[0052] This example evaluates the antibacterial properties of kaolinite-based metal ion antibacterial medical gauze.
[0053] Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) were used as representatives of Gram-negative and Gram-positive bacteria, respectively, to evaluate the antibacterial activity of kaolinite-based metal ion antibacterial medical gauze. The antibacterial properties of different materials were evaluated by plate coating experiments. A single colony was dispersed in 10 ml of culture medium and cultured in a constant temperature shaker (37°C) for 12 hours. Then, the cultured bacterial solution was diluted (10 5-6 CFU mL -1 Finally, 1×1 cm kaolinite-based metal ion antibacterial medical gauze was placed in the center of the plate, and the bacterial growth was observed after constant temperature culture at 37°C for 24 hours.
[0054] The area of the inhibition ring (cm 2) evaluated the antibacterial effect of kaolinite-based metal ion antibacterial medical gauze on Escherichia coli (E.coli) and Staphylococcus aureus (S.aureus), and the results are shown in Table 4. The larger the antibacterial ring area produced by the kaolinite-based metal ion antibacterial medical gauze, the better the antibacterial effect of the kaolinite-based metal ion antibacterial medical gauze of the present invention and the longer-term bactericidal effect, especially the more obvious antibacterial effect on Staphylococcus aureus (S.aureus). In addition, the load of mixed metal ions can overcome the limitations of the limited antibacterial function of a single metal ion in a complex biological environment, because the mixed metal ions can realize charge coupling between them, regulate the electronic structure of the antibacterial ions, and then optimize the antibacterial effect. Among them, the antibacterial effect of the silver-based composite ions is more obvious, thanks to the excellent antibacterial properties of the silver-zinc antibacterial material itself and the functional characteristics such as non-toxicity, safety and long-term stability.
[0055] Table 4 Inhibitory ring area (cm2) of kaolinite-based metal ion antibacterial medical gauze against different bacteria 2 )
[0056]
[0057] For matters not mentioned above, the prior art applies.
[0058] The present invention is based on the research of project 2023YFE0202600 on the preparation of new antibacterial hemostatic composite materials by natural nanostructure microfluidic assembly. Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are only for illustration, not for limiting the scope of the present invention. Those skilled in the art to which the present invention belongs can make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined in the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing kaolinite-based antibacterial medical gauze, characterized in that: The steps include: Step S1, preparing micron-sized flaky kaolinite by a step-by-step intercalation-ultrasonic exfoliation-grading centrifugation method; Step S2, loading antibacterial metal ions on micron-sized flaky kaolinite after modification with polyacrylic acid to obtain kaolinite-based metal ion antibacterial material; Step S3, preparing a mixed solution of kaolinite-based metal ion antibacterial material, polyvinyl pyrrolidone and sodium carboxymethyl cellulose, then soaking the medical non-woven fabric in the mixed solution, taking it out and drying it to obtain kaolinite-based metal ion antibacterial medical gauze.
2. The preparation method according to claim 1, characterized in that: The concentration of the mixed solution of polyvinyl pyrrolidone and sodium carboxymethyl cellulose polymer is 0.1% to 1%.
3. The preparation method according to claim 1, characterized in that: The mass ratio of polyvinyl pyrrolidone to sodium carboxymethyl cellulose is 1-3:1-3.
4. The preparation method according to claim 1, characterized in that: In the mixed solution of step S3, the concentration of the kaolinite-based metal ion antibacterial material is 8 to 15 mg / mL.
5. The preparation method according to claim 1, characterized in that: The antibacterial metal ions include one or more of silver, zinc and gallium.
6. The preparation method according to claim 1, characterized in that: The specific operation of step S2 is: adding the polyacrylic acid aqueous solution dropwise into the kaolinite aqueous dispersion to stir the reaction, then adding the antibacterial metal ion solution to stir the reaction, and after the reaction is completed, centrifugation washing and freeze drying are performed to obtain the kaolinite-based metal ion antibacterial material.
7. The preparation method according to claim 6, characterized in that: The mass ratio of polyacrylic acid to kaolinite is 0.5-3:1, the concentration of antibacterial metal ions is 1 mol / L, and the reaction time is 3-6 hours.
8. The preparation method according to claim 1, characterized in that: In step S1, the intercalation agents used in the stepwise intercalation process are dimethyl sulfoxide and urea, respectively, and the intercalation reaction time is 20 to 24 hours; and\or, The ultrasonic power during the ultrasonic stripping process is 1200-1500W, the ultrasonic time is 4-6h, and the reaction temperature is 50-60°C.
9. The preparation method according to claim 1, characterized in that: In step S1, the centrifugal speed during the graded centrifugation process is 1000-6000 rpm, and the centrifugal time is 3-5 min.
10. A kaolinite-based antibacterial medical gauze prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Cited By
Ionic cross-linked network cured composite hemostatic gauze and preparation method thereof
CN121971681A
